Types of intrapartum hypoxia in the newborn at term with metabolic acidemia: A retrospective study - Léa Descourvieres; Louise Ghesquiere; Elodie Drumez; Claire Martin; Audrey Sauvage; Damien Subtil; Véronique Houfflin‐Debarge; Charles Garabedian (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In the most recent recommendations of the International Federation of Gynecology and Obstetrics (FIGO), a chapter was dedicated to the physiological approach and to the description of fetal mechanisms developed to respond to hypoxia. Our objective was to classify the type of hypoxia in the case of metabolic acidemia and to describe the order of appearance of fetal heart rate abnormalities in cases of gradually evolving hypoxia. Material and methods 132 neonates born between 2018 and 2020 with acidemia were included. We excluded preterm birth, fetuses with congenital anomaly and twin pregnancies. Intrapartum cardiotocography traces were assigned to one of these four types of labor hypoxia: acute, subacute, gradually evolving and chronic hypoxia. For gradually evolving hypoxia, fetal heart rate abnormalities were described according to the FIGO classification. Results 36 cardiotocography traces (27.3%) were classified as acute hypoxia, 14 (10.6%) as subacute hypoxia, and 3 (3.2%) as chronic hypoxia; gradually evolving hypoxia occurred in 62 cases (47%). In 77.4% of cases of gradually evolving hypoxia, deceleration was the first anomaly to appear, with loss of variability and bradycardia appearing later. Increased fetal heart rate was observed immediately after late deceleration in 46.8% of cases and was followed by a loss of variability or saltatory rhythm in 37.1% of cases. Conclusions In cases of metabolic acidemia at term, the most frequent situation observed was gradually evolving hypoxia, with an initial occurrence of decelerations. The sequence of fetal heart rate modifications was variable.